DIVIDEND PAYOUT, LEVERAGE AND EQUITY MARKET VOLATILITY AMONG FIRMS LISTED AT THE NAIROBI SECURITIES EXCHANGE, KENYA - Justin Orang’i Ombui; Gordon Opuodho; Isaac Linus Ochieng (ZILLZELL MEDIA PRIMA, 2025)
This study investigates the effect of dividend payout on equity market volatility among firms listed on the Nairobi Securities Exchange, considering leverage as a moderating variable. Applying panel regression techniques alongside comprehensive diagnostic testing, the study finds that dividend payout significantly reduces volatility, confirming the stabilizing role of dividends in emerging markets. The inclusion of firm size strengthens the model, showing that larger firms experience lower volatility, while leverage increases volatility but also enhances the stabilizing effect of dividends. These findings support dividend signalling and bird-in-hand theories by demonstrating that stable and predictable payouts help to calm investor uncertainty. The study contributes to the theoretical debate by clarifying the dual role of dividend payout as both a stabilizing mechanism and a signalling tool, while practically recommending stronger dividend disclosure practices and prudent leverage management to mitigate volatility in frontier markets.